Deaths and disability-adjusted life years burden attributed to air pollution in China, 1990–2019: Results from the global burden of disease study 2019 - Gan, Hui; Cheng, Long; Zhai, Yingying; Wang, Yimin; Hu, Haisheng; Zhu, Zheng; Sun, Baoqing (Frontiers in Environmental Science, 2022)
Background: The deaths and disability adjusted life years (DALYs) impact of air pollution in China is not well elucidated. We aimed to analyze the association of air pollution with death and DALYs for Chinese population. Methods: We extracted data about the deaths and disability adjusted life years burden attributed to air pollution in the previous 30 years in China from the Global Burden of Disease (GBD) study 2019 and performed a comprehensive analysis and summary. Results: 1.85 (95% UI: 1.57-2.17) million Chinese people lost their lives as a results of air pollution in 2019, a slightly decrease from 1990. In 2019, the Disability-adjusted life years (DALYs) caused by air pollution in China was 42.51 (95% UI: 36.34-49.48) million, 30.2% decrease from 1990. From 1990 to 2019, both ASDR and age standardized-DALYs due to air pollution in China showed a significant year-on-year downward trend. Air pollution-related deaths and DALYs occurred most in people over the age of 50. Stroke, ischemic heart disease and chronic obstructive pulmonary disease attributed the most death burden by air pollution in China in 2019. Conclusions: Over the past 30 years, air pollution has brought a heavy disease burden to China, and in the future, joint efforts will be required to improve the quality of control.